A new species and two new records of Argyresthia Hübner, [1825] (Lepidoptera: Argyresthiidae) from Hallasan National Park of Korea - Lee, Ga-Eun; Lee, Yeong-Don; Liu, Tengteng (Zootaxa, 2023)
Argyresthia Hübner, [1825] is a genus of small to medium sized glossy moths which comprises more than 200 species worldwide, but the Korean fauna includes only eight previously known species. In this study, we describe one new species, A. (Argyresthia) brevalbella sp. nov., and report A. (A.) angusta Moriuti, 1969 and A. (Blastotere) densa Liu, Wang et Li, 2017 for the first time from the country. The three species were found in Hallasan National Park located in the southernmost province Jeju-do at altitudes between 900–1,300 m. The new species is externally very similar to A. (A.) longalbella Liu, Wang et Li, 2017 in having a fuscous forewing with a white dorsal band, but can be distinguished by the shape of the valva, saccus and phallus of the male genitalia. We provide photographs of adults and genitalia, differential diagnoses and DNA barcodes for the three species.